TRENDS AND CHALLENGES OF BRAZILIAN PELLETS INDUSTRY ORIGINATED FROM AGROFORESTRY - Garcia, Dorival Pinheiro [UNESP]; Caraschi, Jose Claudio [UNESP]; Ventorim, Gustavo [UNESP]; Antunes Vieira, Fabio Henrique [UNESP] (Univ Federal Lavras-ufla, 2016)
Wood pellets are biofuels produced from agroforestry waste such as sugarcane bagasse, wood sawdust and shavings. They are compressed biofuels that have low moisture, allowing high combustion efficiency, especially because they are natural products of easily handling with high energy density. To explore pellets opportunities in Brazil (production and marketing), it is necessary to provide information about the chemical and energy characteristics, technologies, prices and prospects of this market. Thus, this article aims to organize and make this information available, enabling general knowledge on the subject and subsidize more investment in the biofuels sector; mostly by adding value to agroforestry waste, available in large volumes in this country. The results showed a young industry, with sixteen plants and production of 49.39 ktonnes of pellets in 2014, but using only 25.5% of its annual production capacity.
Keywords: Biomass; Renewable energy; Wood pellets; Agropellets